Бабу-л-харф в труде Джамаледдина Мухаммед ибн Абдулгани аль-Ардебили "Шарху-Л-Унмузадж Фи-Н-Нахв " Babu-l-harf in jamaladdin mohammed ibn abdulgani al-Ardebili`s work «Sharkhu -L-Unmuzadj Fi-N-Nakhv» (Вестник КазНУ. Серия Востоковедения, 2016)
The article is dedicated to the topic of “babu-l-harf” in “Sharhu-l-Unmuzaj fi-n-nahv” of distinguished Azerbaijani arabic linguistJamaleddin Muhammed ibn Abdulghani al Ardabili who lived in the end of XII and in the first half of XIII centures. In order tobring some explanation to grammatical problems there were mentioned works of classic linguists as Halil Ibn Ahmad, Ferra andSebaweyh in the article. This article is very important from viewpoint of research of nearly eight centures old resourse and investigationof conditions of Azerbaijani linguistic science in Middle Ages, also revealment of that period’s linguists’ importance in the developmentof Arabic linguistics.
Keywords: Джамаледдин Мухаммед ибн Абдулгани аль-Ардебили "Шарху-Л-Унмузадж Фи-Н-Нахв"